Diagnostic accuracy of stool Xpert MTB/RIF for detection of pulmonary tuberculosis in children: a Systematic Review and Meta-analysis - MacLean, Emily; Sulis, Giorgia; Denkinger, Claudia M.; Khan, Faiz Ahmad (Journal of clinical microbiology, 2019)
Invasive collection methods are often required to obtain samples for the microbiological evaluation of children with presumptive pulmonary tuberculosis (PTB). Nucleic acid amplification testing of easier-to-collect stool samples could be a noninvasive method of diagnosing PTB. We conducted a systematic review and meta-analysis to evaluate the diagnostic accuracy of testing stool with the Xpert MTB/RIF assay (“stool Xpert”) for childhood PTB. Four databases were searched for publications from January 2008 to June 2018. Studies assessing the diagnostic accuracy among children of stool Xpert compared to a microbiological reference standard of conventional specimens tested by mycobacterial culture or Xpert were eligible. Bivariate random-effects meta-analyses were performed to calculate pooled sensitivity and specificity of stool Xpert against the reference standard. From 1,589 citations, 9 studies (n = 1,681) were included. Median participant ages ranged from 1.3 to 10.6 years. Protocols for stool processing and testing varied substantially, with differences in reagents and methods of homogenization and filtering. Against the microbiological reference standard, the pooled sensitivity and specificity of stool Xpert were 67% (95% confidence interval [CI], 52 to 79%) and 99% (95% CI, 98 to 99%), respectively. Sensitivity was higher among children with HIV (79% [95% CI, 68 to 87%] versus 60% [95% CI, 44 to 74%] among HIV-uninfected children). Heterogeneity was high. Data were insufficient for subgroup analyses among children under the age of 5 years, the most relevant target population. Stool Xpert could be a noninvasive method of ruling in PTB in children, particularly those with HIV. However, studies focused on children under 5 years of age are needed, and generalizability of the evidence is limited by the lack of standardized stool preparation and testing protocols.
Gesehen am 27.06.2019